The Influence of Teachers' Professional Development Towards Teacher’s Participation in Program Sekolah Penggerak Development - Triana, Hana; Marini, Arita; MS, Zulela (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to analyze the form of teacher competence professional development towards participation in developing professionalism in the driving school program. This research method uses quantitative methods while quantitative descriptive analysis is carried out on 20 respondents. Interpretation of survey data to identify forms of teacher professional development, expected funding sources and participation in training on implementation of driving schools facilitated by Expert Trainers which are part of mandatory activities in the implementation of the independent curriculum and/or support from the regional/central government or other forms of activity facilitated by the organization or other communities.